Design and Build E-Stm Using Real-time Push Notification in Sumber Padi Village - Wulandari, Novika; Samsudin, Samsudin (Politeknik Piksi Ganesha Indonesia, 2024)
Relief societies (STM) are important in helping people in need through various social programs and activities.This study addresses the issue of STM member logging and financial data management, then addressing misinformation reported by managers or citizens and making it easier for citizens to pay STM dues. This study uses Firebase Realtime database for data storage and Firebase Storage to store photo media; Research and development methods (R&D used as a method in this study, and uses the Rapid Application Development (RAD) method as its system development method. The author also uses Realtime push Notification by using firebase cloud messaging to build STM applications. The results of the black box system test show that the application runs by the needs of the system, the research carried out has high relevance to facilitate the management of member data, contributions and activity information on STM.